Flexibility in the Social Structure of Male Chimpanzees (Pan troglodytes schweinfurthii) in the Budongo Forest, Uganda - Badihi, Gal; Bodden, Kelsey; Zuberbühler, Klaus; Samuni, Liran; Hobaiter, Catherine (Royal Society Open Science, 2022)
Individuals of social species experience competitive costsand social benefits of group living. Substantial flexibility inhumans’social structure and the combination of differenttypes of social structure with fission–fusion dynamics allowus to live in extremely large groups—overcoming some ofthe costs of group living while capitalizing on the benefits.Non-human species also show a range of social strategies todeal with this trade-off. Chimpanzees are an archetypicalfission–fusion species, using dynamic changes in day-to-day association to moderate the costs of within-groupcompetition. Using 4 years of association data from twoneighbouring communities of East African chimpanzees (Pantroglodytes schweinfurthii), we describe an unexplored level offlexibility in chimpanzee social structure. We show thatmales from the larger Waibira community (N=24–31)exhibited additional structural levels of semi-stable core–periphery society, while males from the smaller Sonsocommunity (N=10–13) did not. This novel core–peripherypattern adds to previous results describing alternativemodular social structure in other large communities ofchimpanzees. Our data support the hypothesis thatchimpanzees can incorporate a range of strategies in additionto fission–fusion to overcome costs of social living, and thattheir social structures may be closer to that of modernhumans than previously described.
Keywords: Group-living; sociality; Social network analysis; Primate